Effects of potassium application on soil ecological resistance to Verticillium wilt of cotton (Gossypium hirsutum L.). Issue 4 (21st March 2022) - Ju, Feiyan; Li, Yan; Zhang, Xihe; Yu, Kai; Huo, Yuyang; Zhu, Junjun; Wang, Youhua; Zhou, Zhiguo; Ali, Saif; Tang, Qiuxiang; Chen, Binglin
ABSTRACT: Verticillium wilt (V-wilt) causes huge and irreparable losses to cotton worldwide every year. Potassium (K) is considered to be a critical nutrient for resistance to biotic and abiotic stresses. To verify the effect of K application on the establishment of an ecological-friendly soil microenvironment resistant to V-wilt, a two-year field experiment was conducted. Two cotton varieties (ND-601, resistive and JM-11, sensitive) with different resistance to V-wilt were used in this study, and five different K rates (0, 75, 150, 225, and 300 kg ha −1 K2 O) were set for each variety in the field inoculated with Verticillium dahliae ( V. dahliae ). The results showed that different levels of K application had significant effect on the reduction of cotton V-wilt. K application increased the content of K and total phenolics in rhizosphere soil, but decreased the content of soluble sugar and alanine. Moreover, K application reduced the number of bacteria, fungi, and total microorganisms in rhizosphere soil, especially the number of V. dahliae . In conclusion, K application can create a good micro-ecological environment for the root system by changing the K status, root exudates, and microorganisms in rhizosphere soil, which are beneficial to reduce the symptoms of cotton V-wilt.